Perceptions of community dementia friendliness: A cross‐sectional study of people with dementia, family caregivers, service providers, and the general public in Taiwan. (12th July 2021) - Liu, Hsin‐Yun; Huang, Hsiu‐Li; Chiu, Yi‐Chen; Tang, Li‐Yu; Hsu, Jung‐Lung; Wu, Suh‐Mian; Lin, Yi‐Hui; Lin, Hsin‐Yi; Su, I‐Ching; Shyu, Yea‐Ing L.
Abstract: Promoting dementia‐friendly communities is an important strategy for improving quality of life for people with dementia and dementia‐family caregivers. The process of building dementia‐friendly communities should include all people living in the community. The objective of this study was to compare perceived dementia friendliness in the community among people with dementia, family caregivers, service providers, and the general public. In Taiwan, we surveyed 60 people with dementia, 140 family caregivers, and 200 members of the general public face to face, with 200 service providers surveyed by mail. Participants completed the Perceived Community Dementia Friendliness measure, consisting of seven subscales: care services, community members, community environment, community interactions, transportation, hospitals, and stores and organisations. This measure has acceptable convergent validity, construct validity, and internal consistency reliability for use in Taiwan. Differences in perceived dementia friendliness were examined by chi‐square tests/analysis of variance. Among the seven subscales, hospitals were rated with good dementia friendliness by 70% of people with dementia ( n = 42); however, care services were rated poor by 23.3% of people with dementia ( n = 14). Hospitals were also rated with good dementia friendliness by 39.2% of family caregivers ( n = 54). Care services were rated as having good dementia friendliness by 43.5% of service providers ( n = 87) and 47% of the general public ( n = 86). Furthermore, community interactions were rated as good by small percentages of family caregivers (11.4%, n = 16), service providers (22.2%, n = 44), and the general public (30.9%, n = 58). Family caregivers, service providers, and the general public rated hospitals with the highest mean dementia‐friendliness score and community interactions with the lowest. Perceived community‐dementia friendliness among participants with dementia differed from that of participants without. People with dementia prioritised improving care services, while people without dementia rated facilitating community interactions as more vital. These differences provide vital insights into understanding the policies and administration of dementia‐friendly communities.